ANALISA DAN PERANCANGAN SISTEM PENILAIAN KINERJA KARYAWAN UNTUK MENINGKATKAN PRODUKTIVITAS KERJA PADA HOTEL BEST WESTERN PLUS MAKASSAR BEACH - Wiputri, Gratiana (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2019)
The main goal of this thesis is to model a system of performance assessment of the Best Western Hotel employees in accordance with the assessment procedure that runs employee tasks and in accordance with each Department so that the employee productivity increases.Keywords: Employee Work Productivity, KPI, Performance Appraisal.